Lightweight cryptography for security and privacy : third International Workshop, LightSec 2014, Istanbul, Turkey, September 1-2, 2014, Revised selected papers /: third International Workshop, LightSec 2014, Istanbul, Turkey, September 1-2, 2014, Revised selected papers. (2015) - Unknown
No abstract available